Monitoring the ingredient change during the production of Tan Re Qing capsules from Scutellariae Radix by HPLC-MS/MS. Issue 17 (8th November 2018) - Qiao, Li-Man; Lou, Dan; Liu, Hong-Wei; Zhang, You-Ting
Abstract: Tan Re Qing (TRQ), a traditional Chinese medicine formula, is composed of Scutellariae Radix and other four herbs (bear bile powder, Caprae Hircus Cornu, Lonicerae japonicae Flos and Forsythiae Fructus ) used for the treatment of bronchitis and upper respiratory infection. Chemical constituents in the herb always changed in content during processing. So, in this study, the ingredient change was monitored from three froms of Scutellariae Radix, including original herb, intermediate and product (TRQ capsules) with the same batch by HPLC MS/MS. A total of 98 compounds, including 69 flavonoids, 5 phenylethanoid glucosides, 6 other compounds and 18 unknown components, were tentatively identified in Scutellariae Radix . Most minor components in Scutellariae Radix were disappeared during preparation process, and only 17 of these compounds were detected in TRQ capsules. 5, 2'-Dihydroxy-7, 8-dimethoxyflavone and one unknown compound were detected in the original herb and intermediate, but disappeared in the TRQ capsules. These findings indicated the productive process control is vital for risk assessment and chemical material basis, as well as the basis for quality control of TRQ capsules. Graphical Abstract: